Maintenance and Mutability amongst Specialist Potters on the Northeast Coast of New Guinea. Issue 2 (25th September 2017) - Gaffney, Dylan
Abstract : This paper examines a central concern in archaeological research: the interplay between technological and social flux over the longue durée . This is done by describing ceramic technological continuity and change, and its correspondence with broader social processes, on the northeast coast of New Guinea in the recent past. It presents new ethnographic information from Madang, Papua New Guinea, involving Bilbil and Yabob potters, to outline the chaîne opératoire of pottery production at present. Comparisons with ethnohistorical texts then allow us to model technological change over a longer period of c. 150 years, following the direct historical approach. This shows distinct continuity, but also substantial modification throughout the nineteenth–twenty-first centuries, as the potters negotiated major social upheavals during the colonial and post-independence periods, such as forcible relocation from their offshore islands onto the mainland. This expands our understanding of how social and technological change can take place amongst small-scale, part-time pottery specialists over the longue durée and how this change is reflected in the finished products and raw materials.